2014
DOI: 10.1103/physrevlett.112.105503
|View full text |Cite
|
Sign up to set email alerts
|

Soft Modes and Nonaffine Rearrangements in the Inherent Structures of Supercooled Liquids

Abstract: We find that the hierarchical organization of the potential energy landscape in a model supercooled liquid can be related to a change in the spatial distribution of soft normal modes. For groups of nearby minima, between which fast relaxation processes typically occur, the localization of the soft modes is very similar. The spatial distribution of soft regions changes, instead, for minima between which transitions relevant to structural relaxation occur. This may be the reason why the soft modes are able to pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 35 publications
4
31
0
Order By: Relevance
“…This result leads us to speculate that soft spots are robust features within a metabasin [23][24][25]. Earlier, we showed that the distribution of soft-spot lifetimes features a power-law tail, and we argued that this feature implies that a single rearrangement does not suffice to destroy a single soft spot.…”
Section: Discussionmentioning
confidence: 98%
“…This result leads us to speculate that soft spots are robust features within a metabasin [23][24][25]. Earlier, we showed that the distribution of soft-spot lifetimes features a power-law tail, and we argued that this feature implies that a single rearrangement does not suffice to destroy a single soft spot.…”
Section: Discussionmentioning
confidence: 98%
“…It has been shown that the local liquid-like (high mobility) regions can act as "plasticity carriers" [27] and shearing amorphous systems can allow the observation of some (otherwise elusive) long-range correlations in a colloidal glass [28]. In both experiments and computer simulations, locally "soft" and "hard" regions of the system, characterized by normal vibrational modes of inherent structures (soft modes) [29][30][31][32], configurational fluctuations that are susceptible to stress driven shear transformations (shear transformation zones, STZs) [33][34][35] and localized regions of strong deformations (hot spots) [36] have been shown to play a key role in the dynamics of supercooled liquids and the mechanics of amorphous solids. These can be used to predict when and where deformations will take place in sheared systems [37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…In both experiments and computer simulations, locally "soft" and "hard" regions of the system, characterized by normal vibrational modes of inherent structures (soft modes) [29][30][31][32], configurational fluctuations that are susceptible to stress driven shear transformations (shear transformation zones, STZs) [33][34][35] and localized regions of strong deformations (hot spots) [36] have been shown to play a key role in the dynamics of supercooled liquids and the mechanics of amorphous solids. These can be used to predict when and where deformations will take place in sheared systems [37][38][39][40]. Recently, shear has been used to access the so-called Gardner transition [41] between glass states with differing stabilities [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…In several quasi-2D or 3D models of amorphous solids (such as jammed packings of soft spheres interacting via repulsive potentials or colloidal particles), low-frequency vibrational normal modes have been characterized, and it has recently been demonstrated that some of these modes are quasilocalized (7)(8)(9)(10)(11)(12)(13)(14). A population of "soft spots" has been identified among them in terms of their low-energy barriers for local rearrangements (13,14), correlating also with properties in supercooled liquids such as dynamic heterogeneity (15)(16)(17). However, it is not certain where the soft spots are in realistic MGs (18), in terms of an explicit correlation with local atomic packing and topological arrangements (18)(19)(20).…”
mentioning
confidence: 99%